2021
DOI: 10.1002/ajp.23237
|View full text |Cite
|
Sign up to set email alerts
|

Food availability, plant diversity, and vegetation structure drive behavioral and ecological variation in Endangered Coimbra‐Filho's titi monkeys

Abstract: There is wide variability in primate behavior and ecology. Understanding how frugivorous primates behave under different habitat fragmentation levels is key for effective conservation and management of species and their habitats. We evaluated the seasonality in activity budget, diet, and ranging behavior of two groups of Endangered Coimbra-Filho's titi monkeys (Callicebus coimbrai). One group inhabited a 14-ha forest fragment, whereas the other lived in a 522-ha fragment. We measured the monthly density of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In our review, habitat degradation affected the behaviour of mammals with a wide range of body mass, ranging from Chiroptera to Proboscidea (0.01–6100 kg). We found that the effect size for habitat degradation on omnivorous species was the largest, which may be because they are more sensitive to the reduction in food resource availability due to their food habits and seasonal differences in time spent foraging, resting and travelling caused by the seasonal phenology (Souza‐Alves et al, 2021). Hence, we suggest integrating animal foraging ecology principles into landscape design and management, in particular for omnivore species, to maintain their natural resource acquisition and reproduction success in areas where habitat modification is inevitable.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our review, habitat degradation affected the behaviour of mammals with a wide range of body mass, ranging from Chiroptera to Proboscidea (0.01–6100 kg). We found that the effect size for habitat degradation on omnivorous species was the largest, which may be because they are more sensitive to the reduction in food resource availability due to their food habits and seasonal differences in time spent foraging, resting and travelling caused by the seasonal phenology (Souza‐Alves et al, 2021). Hence, we suggest integrating animal foraging ecology principles into landscape design and management, in particular for omnivore species, to maintain their natural resource acquisition and reproduction success in areas where habitat modification is inevitable.…”
Section: Discussionmentioning
confidence: 94%
“…On the one hand, reduced natural resource availability in fragmented habitats is a major cause of change in animals' foraging time. For example, Coimbra‐Filho's titi monkeys Callicebus coimbrai spent more time foraging in highly fragmented habitats (Souza‐Alves et al, 2021). Altering food availability also led to changes in food selection, such as in bale monkeys Chlorocebus djamdjamensis that spent significantly more time feeding on nonbamboo plants and insects in fragmented forest in response to the relative scarcity of bamboo (Mekonnen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have proposed that the marmosets' activity period may be shortened systematically during periods of reduced food availability, but this has not been tested (Corrêa, 1995; Ferrari & Lopes, 1990; Ferrari, 1988; Guimarães, 1998). Furthermore, the effect of food availability may be site‐specific (Souza‐Alves, Chagas, Santana, et al, 2021), or even absent in some primates (Fernandez‐Duque, 2003). Only one study investigated systematically the influence of environmental temperatures on the free‐ranging marmoset activity period within its natural distribution (de la Fuente et al, 2014) however, the authors did not control for potentially confounding variables such as food availability and predation risk, and took data at a single site.…”
Section: Introductionmentioning
confidence: 99%